2008
DOI: 10.1007/978-3-540-79549-0_27
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement Study of Bandwidth Estimation in IEEE 802.11g Wireless LANs Using the DCF

Abstract: Abstract. In this paper we present results from an extensive measurement study of wireless bandwidth estimation in IEEE 802.11 WLANs using the distributed coordination function. We show that a number of known iterative probing methods, which are based on the assumption of first-come first-serve scheduling, can be expected to report the fair bandwidth share of a new flow rather than the available bandwidth. Our measurement results confirm this view and we conclude that under the current probe gap and probe rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Algorithmic Mechanism Design (AMD) [12] and Distributed Algorithmic Mechanism Design (DAMD) [7] study mechanisms in which the outcome and the payment depend on the input provided by the participants. These participants (called agents) are assumed to be rational (i.e., they want to maximize their profit).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithmic Mechanism Design (AMD) [12] and Distributed Algorithmic Mechanism Design (DAMD) [7] study mechanisms in which the outcome and the payment depend on the input provided by the participants. These participants (called agents) are assumed to be rational (i.e., they want to maximize their profit).…”
Section: Related Workmentioning
confidence: 99%
“…No strategyproof mechanism can be both efficient and budget balanced at the same time [8]. The MC mechanism is recommended when the multicast delivery may be subsidized, if the mechanism runs a budget deficit [7]. Since the MC mechanism does not generate sufficient revenue, it is not a suitable mechanism from the content provider's point of view.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Available bandwidth estimation is a challenging task due to the wireless characteristics such as fading of channel, re-transmission and error from physical obstacles [8] . Wireless channel is shared access medium and available bandwidth varies with the number of host contending for the channel [9] .…”
Section: Available Bandwidth Estimationmentioning
confidence: 99%
“…When considering WLAN environments, various preliminary studies have shown that the application of these results is not straightforward ( [2,3,25]). The main reasons for this reside in the assumptions taken to develop bandwidth measurement models and tools.…”
Section: Introductionmentioning
confidence: 99%